Differential/combined effect of water contamination with cadmium and nickel on tissues of rats - Novelli, ELB; Hernandes, R. T.; Novelli, JLVB; Barbosa, L. L. (Elsevier B.V., 1998)
The contamination of water by metal compounds is a worldwide environmental problem. Concentrations of metals are widely related to biochemical values which are used in disease diagnosis due to environmental toxicity. The acute combined effects of cadmium and nickel on biochemical parameters were determined and compared with those of Cd2+ or Ni2+ alone in rats. Male adult rats were given drinking solutions of CdCl2 [Cd(II) cation, 100 mg/liter] or NiSO4 [Ni(II) cation, 100 mg/liter]. For the combined treatment, the animals (Ni+Cd) received both Ni(II)) cation (100 mg/liter) and Cd(II) cation (100 mg/liter). Nickel treatment induced increased alanine transaminase (ALT) activity and hepatotoxicity, but not renal injury. In contrast, cadmium exposure produced hepatic, renal and myocardial damage, characterized by increased creatinine, total and direct bilirubin concentrations and increased ALT and lactate dehydrogenase (LDH) activities. The combined effect Ni-Cd is less toxic than cadmium alone, suggesting antagonism between these toxicants. The toxicity of nickel and cadmium, alone and in combination, decreased Cu-Zn superoxide dismutase (SOD) activity and increased lipoperoxide formation. (C) 1998 Elsevier B.V. Ltd. All rights reserved.
Keywords: nickel; cadmium; toxicity; superoxide radicals; rats